Pengaruh Ekstrak Metanol Buah Lakum (Cayratia trifolia L. Domin) terhadap Nilai SGOT dan SGPT Tikus Putih Diinduksi Parasetamol - Diah Wulandari Rousdy; Elvi Rusmiyanto Pancaning Wardoyo; Catur Wulandari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Lakum fruit (Cayratia trifolia L. (Domin)) has secondary metabolite compounds that are beneficial to health, one of which is a hepatoprotector. This study was conducted to prove the potential of hepatoprotective activity of lakum fruit methanol extract based on the value of SGPT and SGOT enzyme. The research method used a pre-posttest randomized control group design with a sample of 35 male rats divided into five treatment groups: solvent control group (CMC 0.5%); positive control group (HEPA-Q®); treatment group extract (0,575; 1,15; 1,725 mg/g BW). The treatment of induction of paracetamol and methanol extract of Cayratia trifolia fruit was carried out for 7 days respectively. The results showed that the dose of 1,15 mg/g BW of Cayratia trifolia fruit methanol extract had the most effective deterioration of SGOT and SGPT values with a percentage reduction of SGOT of 49.3% and SGPT of 51.8% (p <0.05) which approached control positive (HEPA-Q®). Based on the research conducted, methanol extract of Cayratia trifolia fruit has the potential to be hepatoprotective.